Oxidative Depolymerization of Alkaline Lignin from Pinus Pinaster by Oxygen and Air for Value-Added Bio-Sourced Synthons - Martin Camus (MDPI AG, 2021)
In this work, an efficient 3-step process targeting the chemical modification and purification of lignin oligomers from industrial alkaline lignin is described. The oxidative depolymerization process of alkaline lignin with O2 or Air pressure, without use of metal catalyst, led to the production of two fractions of lignin oligomers named ‘precipitated lignin’ and ‘hydrosoluble lignin’ with 40% and 60% yield, respectively. These fractions were characterized with a wide range of methods including NMR spectroscopy (31P, 2D-HSQC), SEC (in basic media), FTIR. NMR analyses revealed the presence of carboxylic acid functions at a ratio of 1.80 mmol/g and 2.80 mmol/g for the precipitated and hydrosoluble lignin, respectively, values much higher than what is generally found in native lignin (between 0.2 and 0.5 mmol/g). SEC analyses revealed the formation of low molar masses for the precipitated (2200 g/mol) and hydrosoluble fractions (1500 g/mol) in contrast to the alkaline lignin (3900 g/mol). It is worth noting that the hydrosoluble fraction of lignin is soluble in water at any pH. Both processes (oxygen and air) were successfully scaled up and showed similar results in terms of yield and functionalization.